Evaluation of the safety and effectiveness of an alternative dural substitute using porcine pericardium for duraplasty in a large animal model. (December 2018) - Seo, Youngbeom; Kim, Jin Wook; Dho, Yun Sik; Chowdhury, Tamrin; Kim, Sojin; Park, Chul-Kee
Highlights: Duraplasty is usually performed to prevent cerebrospinal fluid leakage and brain tissue injury after various types of brain surgery. Various materials have been developed and evaluated to determine the ideal dural substitute. The porcine pericardial patch seems to have efficacy and safety as an alternative dura graft compared with a small intestinal submucosal graft. Our study suggests the potential of a new type of dural substitute derived from porcine pericardium. Abstract: This study aimed to evaluate the safety and effectiveness of an alternative dural substitute using a porcine pericardial graft for duraplasty in a large animal model. Six pigs underwent bilateral craniectomy followed by bilateral duraplasty using either a porcine pericardium patch or a Biodesign® Dural Repair Graft. Intraoperative workability was evaluated for each type of graft. Pigs were euthanized after 1 and 3 months ( n  = 3 per group). Histological analysis was performed for each case. The Biodesign® Dural Repair Graft showed better workability than the porcine pericardial patch, which was more transparent (p = 0.002). Histological analyses at 1 and 3 months showed no differences between the types of graft. There was no postoperative leakage of cerebrospinal fluid in any case. No grafts showed any adverse reactions in the underlying brain tissues. The porcine pericardial patch as a dural substitute seems to be an acceptable alternative graft to duraplasty using a small intestinal submucosal graft (Biodesign®). Further studies are needed to determine whether porcine pericardial patches provide workable alternatives in clinical practice.